Conceptual Model Development Of Nexus Between Agile Human Resource Management Practices And Employee’s Empowerment: Contemporary Perception - Ishaq Ibrahim; Walid Abdullah Alsuraihi; Murad Al-zaqeba (TANMEAH BASSMAH PRESS, 2025)
Non-Indexed Publication